Thermochemical conversion of plant biomass in the energotechnological complex with heat recovery - Zablodskiy, Mykola (Array, 2021)
Basic performance principles of the energotechnological complex used for thermochemical conversion of plant biomass with the influence of a magnetic field and high recovery of spent heat carrier energy have been developed. The concurrent saturation of a spent heat carrier in a loading bunker with the steam from humid biomass aimed at using a certain part of a spent heat carrier, which is clear from oxygen and nitrogen oxide, and moisture in thermochemical recovery has been considered as an important aspect of recuperation processes. A mathematical model has been developed and the results of numerical simulation have been presented for determining the distribution of temperature, velocity and pressure fields in a loading bunker. Prospective assessment of the engineering solutions developed for heat energy recovery of a double-flow spent heat carrier has been conducted.